2017
DOI: 10.1038/leu.2017.299
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 regulates microRNA-27b that suppresses proliferation, promotes apoptosis and target MET in diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma. Histone deacetylase 6 (HDAC6) is frequently altered in DLBCL and inhibition of HDAC6 has potent anti-tumor effects in vitro and in vivo. We profiled miRNAs that altered in the HDAC6 knockdown DLBCL cells with NanoString nCounter assay and identified microRNA-27b (miR-27b) as the most significantly increased miRNA. We validated decreased expression of miR-27b in DLBCL tissues, and we found that low expression of miR-27b was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…A recent study has shown that activated transcription factor 3 in association with HDAC6 acts to decrease the transcription of miR‐199a‐2/miR‐214 . HDAC6 also negatively regulates miR‐27b through Rel A/p65 to modulate the MET/PI3K/AKT pathway in diffusing large B‐cell lymphoma . Based on these reports, we hypothesized that loss or suppression of HDAC6, as a potent histone modifier, causes re‐activation of comprehensive functional RNAs, especially oncogenic microRNAs (oncomiRs), and thereby suppresses tumor suppressors contributing to hepatocellular carcinogenesis.…”
mentioning
confidence: 98%
“…A recent study has shown that activated transcription factor 3 in association with HDAC6 acts to decrease the transcription of miR‐199a‐2/miR‐214 . HDAC6 also negatively regulates miR‐27b through Rel A/p65 to modulate the MET/PI3K/AKT pathway in diffusing large B‐cell lymphoma . Based on these reports, we hypothesized that loss or suppression of HDAC6, as a potent histone modifier, causes re‐activation of comprehensive functional RNAs, especially oncogenic microRNAs (oncomiRs), and thereby suppresses tumor suppressors contributing to hepatocellular carcinogenesis.…”
mentioning
confidence: 98%
“…At the molecular level, miR-155 represses the growth-inhibitory effects of bone morphogenetic protein receptor type 2 (BMPR2) and TGF-β in DLBCL cells via direct targeting of SMAD5 [ 180 ], and, in a therapeutic view, ectopic delivery of anti-miR-155 leads to lymphoma regression in a xeno-transplant mouse model [ 181 ]. Recently it was shown that an increased expression of miR-27b , by the histone deacetylase 6 (HDAC6) knockdown, inhibits tumor growth in a DLBCL mouse model, by targeting the MET proto-oncogene, receptor tyrosine kinase (MET)/phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit beta (PIK3CB, also known as PI3K)/AKT oncogenic pathway (MET/PI3K/AKT) [ 182 ]. MiR-26a and miR-181a also display oncosuppressor features.…”
Section: Mirnas In Hematological Malignanciesmentioning
confidence: 99%
“…Accumulating evidence suggested that miRs may be important in the development of malignancies (6). Previous studies demonstrated that miRs are involved in a number of cancer cell biological processes, including metastasis (7), invasion (8), angiogenesis (9), proliferation, apoptosis (10), differentiation (11), metabolism (12) and drug resistance (13). The dysregulation of miRs is observed in the majority of types of cancer, including RCC (14).…”
Section: Introductionmentioning
confidence: 99%